(untitled) (Physical Education, Health and Social Sciences, 2025)
As technology plays a critical role in shaping an individual’s health behaviors, this study examines the mediating role of the adaptation of wearable fitness devices between e-health literacy and physical activities. Moreover, this study also examines the moderating role of trust in technology and health consciousness among Pakistani students. A cross-sectional study was conducted, in which 513 students were recruited and completed the questionnaires. A statistical Hayes PROCESS analysis was used to test the hypothesis. The findings revealed that the students have a moderate level of e-health literacy, the adaption of wearable fitness devices, physical activity, trust in technology, and health consciousness. Moreover, e-health literacy has a significant positive relationship with wearable fitness devices, which mediate the relationship between e-health literacy and physical activity (Beta = 0.54, p = 0.003). Trust in technology moderates the relationship between e-health literacy and wearable fitness devices (Beta = 0.59, P = 0.01), and health consciousness moderates the relationship between wearable fitness devices and physical activity (Beta = 0.41, t = 7.36, P = 0.040).